The use of noninvasive measurements of intracranial pressure in patients with traumatic brain injury: a narrative review - Faria, Bárbara Caroline Dias; Sacramento, Luiz Gustavo Guimarães; Queiroz, André Vitor Rocha; Leite, Fernanda de Andrade Dias; Oliveira, Henrique Lacerda Lage Lopes de; Kimura, Thais Yuki; Faleiro, Rodrigo Moreira (Arquivos de Neuro-Psiquiatria, 2023)
Background The most frequent cause of death in neurosurgical patients is due to the increase in intracranial pressure (ICP); consequently, adequate monitoring of this parameter is extremely important.Objectives In this study, we aimed to analyze the accuracy of noninvasive measurement methods for intracranial hypertension (IH) in patients with traumatic brain injury (TBI).Methods The data were obtained from the PubMed database, using the following terms: intracranialpressure, noninvasive, monitoring, assessment, and measurement. The selected articles date from 1980 to 2021, all of which were observational studies or clinical trials, in English and specifying ICP measurement in TBI. At the end of the selection, 21 articles were included in this review.Results The optic nerve sheath diameter (ONSD), pupillometry, transcranial doppler (TCD), multimodal combination, brain compliance using ICP waveform (ICPW), HeadSense, and Visual flash evoked pressure (FVEP) were analyzed. Pupillometry was not found to correlate with ICP, while HeadSense monitor and the FVEP method appear to have good correlation, but sensitivity and specificity data are not available. The ONSD and TCD methods showed good-to-moderate accuracy on invasive ICP values and potential to detect IH in most studies. Furthermore, multimodal combination may reduce the error possibility related to each technique. Finally, ICPW showed good accuracy to ICP values, but this analysis included TBI and non-TBI patients in the same sample.Conclusions Noninvasive ICP monitoring methods may be used in the near future to guide TBI patients' management.
Keywords: Brain Injuries, Traumatic; Intracranial Pressure; Intracranial Hypertension